The Little mermaid [videorecording] - Ashman, Howard; Clements, Ron.; Muskin, John.; Walt Disney Pictures ([New York] Walt Disney, 1989)
A little sea princess, longing to be human, trades her mermaid's tail for legs, hoping to win the love of a prince and earn an immortal soul for herself.
Based on the fairy tale of Hans Christian Andersen.
Keywords: Fairy tales -- Juvenile films; Animated films; Children's films; Feature films